MENGUAK PSIKOLOGI ISLAM MELALUI PENDEKATAN SEJARAH - Sudirman Sudirman (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2020)
The psychological approach in Islamic studies has a significant role in explaining the external symptoms of religious people. Armed with psychological theories, it will be easy to know the level of religion a person understands, lives and practices. This paper aims to explain and analyze Islamic psychology based on a historical approach and analyze western psychology schools using an Islamic psychological approach. This study refers to the history of Islamic psychology from the 19th century to the modern era at this time, and also how the development of religious psychology. The results in this article are that humans have the potential to do good from the aspects of will, freedom, feelings, and thoughts to reveal the meaning of life based on monotheistic values ??so that humans are able to develop the potential and quality of Islamic life, namely by integrating the pyramid relationship between lust, intellect, and heart into the human psychological context based on the teachings of revelation that will give birth to a creative life as ordered by God in the Koran.